ITER divertor plasma response to time-dependent impurity injection. (August 2017) - Bonnin, X.; Pitts, R.A.; Komarov, V.; Escourbiac, F.; Merola, M.; Bo, L.; Wei, L.; Pan, L.; Kukushkin, A.S.
Highlights: The response of ITER divertor target monoblocks is assessed in response to a sudden plasma re-attachment event rapidly increasing the heat load above design values. The time delay for mitigative action, namely divertor neon impurity gas injection, is measured using a dedicated experimental workbench. The residence time of neon impurities in the divertor is estimated through use of a database of SOLPS4.3 simulations. The neon divertor residence time is found to be roughly inversely proportional to the divertor neutral pressure. Plasma response to the neon injection is calculated by means of SOLPS-ITER time-dependent simulations. Abstract: The ITER divertor, in its full-power operation phase, will need to withstand steady-state heat fluxes of up to 10 MWm −2 . In addition, "slow" plasma transients such as re-attachment events must be considered, during which the surface heat fluxes will increase significantly in a short period of time (∼few seconds). To mitigate such transients, ITER plans to use the divertor gas injection system (GIS) to introduce radiating impurity species (probably using a hydrogenic carrier gas to improve response time) into the divertor plasma. We consider here various aspects of this process. First, we assess the time needed for critical damage to occur to the vertical target monoblocks by considering two limits: surface tungsten melting and critical heat flux to the coolant channel. This provides us with the time limits before which the plasma heat flux must be reduced to tolerable values. A dedicated experimental test bench has been used to measure the travel time of the injected gas from the valve to the divertor subvolume, using a manifold with the same pipe length as envisaged for the actual ITER device and studying a wide range of gas mixtures and throughputs. Once the gas has arrived in the divertor, we use the existing database of SOLPS4.3 simulations of the ITER divertor to estimate, for the case of neon as radiative species, the neon residence time, together with some new time-dependent SOLPS-ITER simulations to assess the time response of the divertor vertical target heat flux.